2017
DOI: 10.3390/ma10101176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Heavy-Duty Scuffing Behavior between Chromium-Based Ceramic Composite and Nickel-Chromium-Molybdenum-Coated Ring Sliding against Cast Iron Liner under Starvation

Abstract: A running-in and starved lubrication experiment is designed to investigate the heavy-duty scuffing behavior of piston ring coatings against cast iron (Fe) cylinder liner using the piston ring reciprocating liner test rig. The scuffing resistance of the piston ring with the chromium-based ceramic composite coating (CKS), and that with the thermally sprayed nickel-chromium-molybdenum coating (NCM) is compared at different nominal pressures (40~100 MPa) and temperatures (180~250 °C). With the failure time as a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…2 the diesel engine works, these special structures can play an important role on lubricating oil reserve and lubricating oil film formation [11][12][13]. In addition, Joshi GS experimentally found that the rougher honing surface resulted in the increase of oil film thickness [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 the diesel engine works, these special structures can play an important role on lubricating oil reserve and lubricating oil film formation [11][12][13]. In addition, Joshi GS experimentally found that the rougher honing surface resulted in the increase of oil film thickness [14].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it can produce a substantially flat or plateau finish on the working surface with much larger bearing area, while maintaining a cross-hatch pattern of valleys for oil retention [9,10]. When the diesel engine works, these special structures can play an important role on lubricating oil reserve and lubricating oil film formation [11][12][13]. In addition, Joshi GS experimentally found that the rougher honing surface resulted in the increase of oil film thickness [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is actually cast iron whose structure lies in the metal matrix and consists of graphite lamellae. The improvement of wear-resistant properties of a cast iron piston ring-cylinder liner pair of an internal combustion engine can exert a significant influence on maintaining service properties, extending service life, and reducing the repair costs [22,23,24].…”
Section: Methodology Applied In Analysing the Chemical Composition Ofmentioning
confidence: 99%
“…One of them focused on wear and coefficient of friction on cylinder liner piston ring on the gray cast iron materials. 3 The results showed that the steady-state wear rate was lower for the piston ring which has the cylinder liner. Aaron et al studied the tribological performance of a flat piston ring prototype with partially textured surface by experimental method.…”
Section: Introductionmentioning
confidence: 97%